Subconjunto terminológico da CIPE® para pessoas com diabetes mellitus na atenção especializada - Ferreira, Luciana Gomes Furtado (2014)
Introduction: The terminological subset of the International Classification for Nursing Practice (ICNP®) are presented as strategies to simplify their use in practice, aiming to develop data describing nursing work, being a reference of ease access in specific care. Objective: To organize a proposal of Terminological Subset of ICNP® people with diabetes mellitus in specialized care based on the Chronic Care Model and Needs Basic Human Theory. Method: Methodological research, organized in four sequence and independent steps. A) Terms and concepts identification important for nursing practice related to the person with diabetes. B) Cross mapping of identified terms with ICNP® terms Version 2011. C) Construction of the statements nursing diagnosis, outcomes and interventions. D) Organization of the Terminological Subset of ICNP® with people with diabetes. Before executed, the project was approved by the Ethic Committee in Research of the University Hospital of UFPB (HULW/UFPB), with CAAE number 1938241300005183. Results: In the first step, there were identified 1.036 terms in 134 records of people with diabetes attended in nursing consultations in the Clinic of Endocrinology of HULW/UFPB, submitted to a normalization process resulting in 582 terms. In the second step, the identified 582 terms were submitted to a cross mapping process, according to ICNP® concepts Version 2011. There were 213 constant terms and 130 not constant terms in this classification, being the database of nursing language terms related to people with diabetes. In the third step, the database, the ICNP® Version 2011 and the Chronic Care Model subsidize the construction of 115 statements of nursing diagnosis/outcomes and 452 nursing interventions. The diagnosis were submitted to evaluation by the specialists about their use in practice and interventions as to their relevance to the corresponding nursing diagnosis. In the fourth step, the organization of the Terminological Subset of ICNP® for people with diabetes in the specialized care, was built by 66 nursing diagnosis/outcomes of and 347 nursing interventions, resulting from the evaluation processes, having as basis the Chronic Care Model and the Needs Basic Human Theory of Horta. Final Considerations: The Terminological Subset of ICNP® resulting research is quite comprehensive, enabling support a diversity of developments in research, including the study of the clinical validation of the diagnosis, the results and interventions as well as their use in the Systematization of Nursing Care Project of HULW/UFPB, as a reference for care and documentation of nursing practice in sectors that assist people with diabetes.